(untitled) (Contemporary Journal of Social Science Review, 2025)
It has been observed language and communication are the tools that contribute to the societal norms. A significant number of studies are available on discourse analysis but limited research is available to explore the discourse analysis of parental communication, the way parents communicate to their sons versus their daughters. Thereby, applying qualitative methodology using Fairclough’s Three-dimensional model, the current study aims to explore the discourse analysis of parental communication. The study highlighted that daughters are often addressed with empathetic language while sons are communicated with assertive and goal-oriented tone. The communication pattern aligns with the traditional South Asian norms.